The 8th European Conference on Antennas and Propagation (EuCAP 2014) 2014
DOI: 10.1109/eucap.2014.6902052
|View full text |Cite
|
Sign up to set email alerts
|

A novel low-profile slot antenna with unidirectional radiation

Abstract: This paper studies the radiation performance of the complementary half-wavelength slot and electric dipole combination with discrete port excitation. With the modified slot ground plane, unidirectional radiation has been achieved. The entire antenna structure can be implemented with a low-profile single-layer PCB board.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Compared to the nonplanar antennas, 9,13,21,37,40,50 the proposed antenna has a relative lower profile and lower configuration. Compared to the antennas with low profile (i.e., height < 0.1λ g ), 22,24,25,39 the proposed antenna has a wider impedance bandwidth, F I G U R E 9 Simulated and measured radiation performances of the antenna prototype, (A) front-to-back ratio, and (B) boresight gain and efficiency higher front-to-back ratio and nearly equal E-and Hplane radiation patterns. In general, it can be concluded that the proposed antenna can exhibit unidirectional radiation with low profile and simple configuration compared to most of the existing complementary dipole antennas.…”
Section: Measurement and Verificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the nonplanar antennas, 9,13,21,37,40,50 the proposed antenna has a relative lower profile and lower configuration. Compared to the antennas with low profile (i.e., height < 0.1λ g ), 22,24,25,39 the proposed antenna has a wider impedance bandwidth, F I G U R E 9 Simulated and measured radiation performances of the antenna prototype, (A) front-to-back ratio, and (B) boresight gain and efficiency higher front-to-back ratio and nearly equal E-and Hplane radiation patterns. In general, it can be concluded that the proposed antenna can exhibit unidirectional radiation with low profile and simple configuration compared to most of the existing complementary dipole antennas.…”
Section: Measurement and Verificationmentioning
confidence: 99%
“…The fourth one is the slot-dipole combined antenna. [29][30][31][32][33][34][35][36][37][38][39][40] A slot radiator cut on the metallic plane serves as a magnetic dipole, 41 while its inherent bi-directional radiation may be a drawback. 42,43 In this case, a metallic cavity box 44 or a plane reflector 45 should be backed one-quarter wavelength to the slot for back lobe suppression and enhanced impedance matching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation